Educação E Luta Política Na Trajetória Do Movimento Dos Trabalhadores Rurais Sem Terra - Perez, Luana De Paula [UNIFESP] (2017)
This Dissertation Aims To Analyze The Relationship Between Education And Political Struggle In The Trajectory Of The Landless Rural Workers Movement (Mst). The Survey Looks At The Issue Of Movement Strategies For Mobilization And To What Extent Education Plays An Important Role In The Correlation Of Forces. Based On Data Collection, Documents And Interviews, It Is Sought To Understand How The Process Of Expansion Of The Educational And Pedagogical Project In The Mst Took Place, Which Is The Relation That Establishes With The Militancy And If The Movement Still Understands Its Struggle Associated With A New Project Of Society. Under The Light Of Concepts Such As Organic Intellectual, Position Warfare And Unitary School, This Research Will Provide An Analysis Of The Relationship Between The Mst And The Conjuncture, Social And Educational Structure, And Changes In The Social Bases That Led The Struggle For Land.